Kinerja Extra-Role dan Kebijakan Kompensasi - Hannah.D Vanzuela Garay (Universitas Islam Indonesia, 2006)
The voluntary and spontaneity behavior of an individual to do errands outside his/her responsibility and current tasks for the sake of his/her organization’s progress is found to be useful in boosting organizational effectiveness. This behavior is known as extra-role performance or organizational citizenship behavior (OCB). However, there are not many re¬searches done to study further on the role of compensation policy in the development of extra-role performance of the individual. The focal point of this article is on the compensation policy process that encourages extra-role performance. Moreover, this article holds the as¬sumption that compensation policy has positive relationship towards the emergence of extra-role performance as being mediated by the satisfaction of individual on the compensation system.Keywords: extra role, compensation policy, satisfaction